Mitigating Skin and Proximity Effect in High-Voltage Underground Segmented Cables Through Individually Insulating Conductor Strings - Soheil Ahmadi; S. H. Khan; K. T. V. Grattan (Energies)
High-voltage underground cables inevitably experience frequency-dependent electromagnetic (EM) losses, driven primarily by skin and proximity effects. These losses become more severe at higher harmonic frequencies, which are increasingly common in modern power networks. In traditional multi-segment cable designs, uninsulated conductor bundles enable large circular eddy current loops that elevate AC resistance and exacerbate both skin and proximity phenomena. This paper investigates the impact of introducing a thin insulating layer between individual conductor strings in a five-segment high-voltage cable model. Two insulation thicknesses, 75 µm and 100 µm, are examined via two-dimensional finite element (FE) harmonic analysis at 0, 50, 150, and 250 Hz. By confining eddy currents to smaller loops within each conductor, the insulating layer achieves up to a 60% reduction in AC losses compared to the baseline uninsulated model, lowering the ratio of AC to DC resistance from about 3.66 down to 1.47–1.49 at 250 Hz. The findings confirm that adding even a modest inter-strand insulation is highly effective at mitigating skin and proximity effects, with only marginal additional benefit from thicker insulation. Such designs offer improved energy efficiency and reduced thermal stress in underground cables, making them attractive for modern power distribution systems where harmonic content is pervasive.